2019
DOI: 10.1016/j.tcr.2019.100229
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal nerve cryoablation for control of traumatic rib fracture pain: A case report

Abstract: Pain from traumatic rib fractures presents a source of major morbidity and mortality. Prior studies have reported 59% of patients continue to have persistent pain at 2 months post injury. Most modern analgesia modalities have short duration of effect (<72 h) and require repeated doses to achieve adequate effect. There are few studies that address long-term analgesia treatment for these injuries. Intercostal cryoneurolysis (IC) is a technique of long-term chest wall analgesia previously studied in thoracic surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…91 Case reports suggest that cryoneurolysis of solely the involved intercostal nerves may provide potent analgesia, thus avoiding the need for hospitalization, obviating opioid requirements, improving breathing/coughing, and therefore decreasing the risk of pulmonary comorbidity. 52,53 Three patients who received cryoneurolysis of the second to fifth intercostal nerves before uni-or bilateral mastectomy reported a near-painless postoperative course without any opioid requirements or sleep disturbances, a significant improvement over historic controls. 54 Ultrasound-guided percutaneous cryoneurolysis may also be used in the extremities, such as to provide analgesia *This retrospective study reported a dramatic difference between the treatment (cryoneurolysis) and control groups, but due to a very small sample size (n = 6), statistics were not applied to the data.…”
Section: Percutaneous Application To Acute Painmentioning
confidence: 99%
“…91 Case reports suggest that cryoneurolysis of solely the involved intercostal nerves may provide potent analgesia, thus avoiding the need for hospitalization, obviating opioid requirements, improving breathing/coughing, and therefore decreasing the risk of pulmonary comorbidity. 52,53 Three patients who received cryoneurolysis of the second to fifth intercostal nerves before uni-or bilateral mastectomy reported a near-painless postoperative course without any opioid requirements or sleep disturbances, a significant improvement over historic controls. 54 Ultrasound-guided percutaneous cryoneurolysis may also be used in the extremities, such as to provide analgesia *This retrospective study reported a dramatic difference between the treatment (cryoneurolysis) and control groups, but due to a very small sample size (n = 6), statistics were not applied to the data.…”
Section: Percutaneous Application To Acute Painmentioning
confidence: 99%
“…The other reason to implement cryoablation is the fact that the patient is already undergoing a surgical procedure, so separate arrangements for the procedure would not be required. The effectiveness of cryoablation in pain management was confirmed by previously published studies and includes rapid pain relief, reduction of narcotic medication, and long-term chest-wall analgesia 19 , 20 . Depending on the extent of the fractures, we ablate from the third up to the ninth intercostal nerve (Fig.…”
Section: Step 2: Preoperative Preparationmentioning
confidence: 54%
“…Furthermore, various treatments of the intercostal nerves were described. These differences are not surprising, since literature on intercostal nerve treatment during SSRF is scarce [ 21 ]. The current sample size was too small to detect differences in clinical and patient-reported outcomes for the various surgical techniques, although it suggests that striving for bridging callus formation in all rib fracture nonunions is associated with a better outcome in terms of pain reduction, which has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, intercostal nerve cryoablation could be considered in this group, given the current rise in positive results for the combination of SSRF with cryoablation. In cryoablation, the intercostal nerve bundles are frozen which induces temporary nerve injury known as axonotmesis, resulting in prolonged analgesia [ 21 , 22 ]. Nevertheless, it should be noted that cryoablation has not been previously investigated specifically in patients with rib fracture nonunion.…”
Section: Discussionmentioning
confidence: 99%